PENGUJIAN DISIPLIN PASAR PERBANKAN BERDASAR POSISI CAR, LDR, ROA DAN NPL - Aditya Febri Riandika, 10.05.52.0018; Taswan, Taswan (Students Journal of Accounting and Banking, 2014)
This study aims to examine the influence of the banks internal analysis of the deposit growth by signaling theory perspective and market discipline. Corresponding signal theory that positive internal conditions increase the confidence that the company has a high quality to attract the interest of the depositors. In this study, researchers used purposive sampling and sample size 349 companies obtain conventional bank in Indonesia, Bank Indonesia registered in the year 2008 to 2012 includes the factors of the Capital Adequacy Ratio (CAR), Loan Deposit Ratio (LDR), Return on Assets (ROA ), and Non-Performing Loans (NPL). Hypothesis testing using t - test with a significance level of 5%. Based on the results of that study showed a significant positive effect of CAR, LDR significant negative effect, significant positive influence ROA and NPL significant negative effect. Keywords: Deposit Growth, Capital Adequancy Ratio, Loan Deposit Ratio, Return on Assets, Non Performing Loan